Relationships of both Heavy and Binge Alcohol Drinking with Unhealthy Habits in Korean Adults Based on the KNHANES IV Data. - Ha-Na Kim; Sang-Wook Song (Tehran University of Medical Sciences, 2014)
We conducted this cross-sectional study to examine the relationships between problematic alcohol drinking, unhealthy habits and socio-demographic factors based on the Fourth Korean National Health and Nutrition Examination Survey (KNHANES IV).We analyzed a total of 13,488 participants based on the data collected from the KNHANES IV performed between 2007 and 2009.The frequency of binge and heavy drinking was significantly higher in men and the married participants with intermediate income. The frequency of binge drinking was higher in younger adults and individuals with at least high school graduates. After the adjustment of socio-demographic factors, the odds of current smoking (adjusted Odds Ratio [aOR] 4.11, 95% CI 3.35-5.03), abdominal obesity (aOR 1.26, 95% CI 1.08-1.48), stress (aOR 1.45, 95% CI 1.261.68), and depressed mood (aOR 1.31, 95% CI 1.08-1.58) were greater in heavy drinkers than in nondrinkers. The odds of current smoking (aOR 1.73, 95% CI 1.42-2.09 for infrequent binge drinking and aOR 4.95, 95% CI 4.25-5.77 for frequent binge drinking), obesity (aOR 1.22, 95% CI 1.06-1.41 for infrequent binge drinking and aOR 1.64, 95% CI 1.46-1.85 for frequent binge drinking), and abdominal obesity (aOR 1.22, 95% CI 1.04-1.43 for infrequent binge drinking and aOR 1.55, 95% CI 1.36-1.77 for frequent binge drinking) were increased with the increased frequency of the binge drinking.Our results would be of help for screening a specific subgroup of individuals who are vulnerable to alcohol drinking by establishing effective population-based strategies to reduce the problematic drinking.